The complete MySQL developer course - Hossain, Mashrur; Percival, Rob ([Packt Publishing], 2018)
"This course will take you on a journey where you'll establish the strongest possible foundation in database development by learning how to use MySQL (the most popular open source database in the world), write queries, create reports, build web applications, and incorporate MySQL as the database layer. Turn your development dreams into a reality by taking this course and putting a check mark next to your growing development skillset. You will learn to Set up MySQL, Work with online IDE's, Create databases and queries, Use logical operators, Manipulate tables/rows/data, Understand how joins work and use them, Create admin features, Implement deployment production and a lot more."--Resource description page